ADAPTASI BENIH IKAN NILA (Oreochromis niloticus) PADA KENAIKAN SALINITAS YANG BERBEDA - Rahmadi Aziz; Epro Barades (Jurnal Perikanan Unram, 2021)
Tilapia fish is a freshwater fish commodity that has the potential to be developed for fisheries business. Tilapia fish have many advantages such as easy breeding, fast-growing, and can survive at high salinity. To increase durability at high salinity it is necessary to prepare saline tilapia seeds produced from parentage that is tolerant to high salinity or through the salination process since the size of the seed. The purpose of this study was to determine the survival rate, absolute growth, and water quality during the adaptation period of increasing salinity of tilapia juvenile. The experimental design used was a completely randomized design with three replications. The salinity increase treatments used were A (1 ppt salinity), B (2 ppt salinity), C (3 ppt salinity), D (4 ppt salinity), and E (5 ppt salinity). The results showed the survival rate of tilapia seeds each treatment is treatment A (1 ppt) by 100%, treatment B (2 ppt) by 100%, treatment C (3 ppt) by 100%, treatment D (4 ppt) by 99.2%, and treatment E (5 ppt) by 98.6%. The results of each absolute growth of each treatment are treatment A (1 ppt) of 0.002 grams / day, treatment B (2 ppt) of 0.002 grams / day, treatment C (3 ppt) of 0.001 grams / day, treatment D (4 ppt) of 0.0007 grams / day, and treatment E (5 ppt) of 0.001 grams / day. It can be concluded that the adaptation of fish seeds at different salinities (1 ppt, 2 ppt, 3 ppt, 4, ppt, and 5 ppt) still shows a good survival rate, but the absolute growth of tilapia seeds on the adaptation of salinity increases of 4 ppt and 5 ppt has not been optimal.